2019
DOI: 10.1002/joc.6280
|View full text |Cite
|
Sign up to set email alerts
|

A 256‐year‐long precipitation reconstruction for northern Kyrgyzstan based on tree‐ring width

Abstract: In this study, 85 tree cores from 45 Schrenk spruces (Picea schrenkiana) were used to establish a regional tree‐ring chronology. A 256‐year pJune–May precipitation (where p denotes a month from the previous year) for northern Kyrgyzstan in central Asia was reconstructed using this newly developed chronology. The tree‐ring‐based precipitation reconstruction tracks the observed data well (r = .622, p < .0001, n = 105). Spatial correlation proved that the reconstructed precipitation series contains climatic signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Rainfall increased during this time, which increased soil moisture and further encouraged the production of cambium cells (Liu et al, 2011). Similar climate responses for the tree species in this study were also reported in northern Kyrgyzstan (Zhang et al, 2019), southern…”
Section: Characteristics Of the Glacier Mass Balance Reconstructionsupporting
confidence: 83%
See 4 more Smart Citations
“…Rainfall increased during this time, which increased soil moisture and further encouraged the production of cambium cells (Liu et al, 2011). Similar climate responses for the tree species in this study were also reported in northern Kyrgyzstan (Zhang et al, 2019), southern…”
Section: Characteristics Of the Glacier Mass Balance Reconstructionsupporting
confidence: 83%
“…According to the results of this research, NAO and ENSO are the primary processes 230 responsible for high-altitude mass balance shifts in the Tuyuksu Glacier. of glacial oscillations are temperature, precipitation and regional climatic inputs (Zhang et al, 2019).…”
Section: Characteristics Of the Glacier Mass Balance Reconstructionmentioning
confidence: 99%
See 3 more Smart Citations